1989
DOI: 10.1111/j.1558-5646.1989.tb02592.x
|View full text |Cite
|
Sign up to set email alerts
|

INBREEDING DEPRESSION IN PARTIALLY SELF‐FERTILIZING PHLOX

Abstract: Inbreeding depression was measured in terms of the relative survivorship of self versus cross seed in 14 Phlox drummondii cultivars and 10 populations of P. cuspidata. The cultivars are predominantly outcrossing; P. cuspidata is predominantly self-fertilizing. The relative survivorship of self versus cross seed averages 0.84 in the cultivars and 0.99 in P. cuspidata. In wild P. drummondii, the average is 0.83. The mean number of lethal equivalents per zygote averages 0.69 in the cultivars and 0.05 in P. cuspid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…P. cuspidata is relatively diminutive in stature with smaller pink flowers and shorter styles (mean ± SE, 0.66 ± 0.10 mm, N = 4). It is self-compatible and has been documented to have high selfing rates in the field (Levin 1978(Levin , 1989a. In contrast, P. drummondii is taller and displays larger red flowers with much longer styles (mean ± SE, 1.56 ± 0.06 mm, N = 4) and is self-incompatible.…”
Section: Methodsmentioning
confidence: 86%
“…P. cuspidata is relatively diminutive in stature with smaller pink flowers and shorter styles (mean ± SE, 0.66 ± 0.10 mm, N = 4). It is self-compatible and has been documented to have high selfing rates in the field (Levin 1978(Levin , 1989a. In contrast, P. drummondii is taller and displays larger red flowers with much longer styles (mean ± SE, 1.56 ± 0.06 mm, N = 4) and is self-incompatible.…”
Section: Methodsmentioning
confidence: 86%
“…Several studies have shown significant inbreeding depression at different stages of the life cycle of flowering plants under laboratory and field conditions (reviewed in Husband and Schemske 1996;Crnokrak and Roff 1999;Keller and Waller 2002). In theory, the early stages of the life cycle should experience the largest decrease in fitness due to inbreeding because the negative effects of genetic load are often expressed early in ontogeny (Shields 1982;Levin 1989). For instance, most results indicate the progeny derived from selfing exhibit reduced performance in comparison with the progeny derived from outcrossing.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, in the rare Aster furcatus, differences between individuals and populations with respect to sporophytic self-incompatibility have been reported to be associated with bottleneck-induced depletion of allelic diversity at the self-incompatibility locus (Reinartz and Les, 1994). Finally, Levin (1975Levin ( , 1989 has reported variation in autogamous seedset in Phlox drummondii, a species with gametophytic self-incompatibility. This variation is heritable and probably caused by modifier alleles at genes other than the self-incompatibility locus (Bixby and Levin, 1996).…”
mentioning
confidence: 94%
“…Partially self-fertile plants have been observed in many species that are normally self-sterile (reviewed by Lloyd and Schoen, 1992;Levin, 1996). Additionally, in several crop species, selective breeding of partially self-fertile individuals from otherwise self-incompatible cultivars has resulted in the formation of self-fertile lines (Robacker and Ascher, 1978;Dana and Ascher, 1985;Rick, 1988).…”
mentioning
confidence: 96%
See 1 more Smart Citation